Quinic and Digallic acids from Pistacia atlantica Desf. Leaves Extracts as Potent Dual Effect Inhibitors against main Protease and RNA-dependent RNA Polymerase of SARS-CoV-2 - Benguechoua, Mebarka I.; Benarous, Khedidja; Benahmed, Ziyad; Boukhalkhal, Sarah; Silva, Artur M. S.; Yousfi, Mohamed (Current Computer - Aided Drug Design, 2022)
Background: Through this study, the Chemical composition realized by UHPLC-DADESI- MSn allowed the detection of different phenolic compound groups from Pistacia atlantica Desf. leaves extracts. We studied the inhibition of main protease (CL3 Mpro) and RNA-dependent RNA polymerase (RdRp) of the SARS-CoV-2 by the identified molecules through molecular docking. Objective: The objective of this study is to identify compounds from Pistacia atlantica Desf. leaves extracts, which might have anti-viral effects. Methods: Chemical composition was realized by UHPLC-DAD-ESI-MSn, and the inhibition of the main protease (CL3 Mpro) and RNA-dependent RNA polymerase (RdRp) of the SARS-CoV-2 was studied using molecular docking with Autodock Vina software. ADMET analysis was carried out. Results: The identified compounds are quinic acid, digallic acid, galloylquinic acid, gallic acid, trigallic acid, digalloylquinic acids, trigalloylquinic acids and methyl gallate; digallic and quinic acids are the best inhibitors. Digallic acid had binding affinity energy (BAE) of -8.2 kcal/mol, and Ki of 1μM for the CL3 Mpro, Ki of 0.62 mM for the RdRp. Quinic acid showed Ki of 4.6 mM, recorded for both enzymes. Through ADMET analysis, we have found that the two molecules are good drug candidates. Conclusion: This is the first time that a group of identified compounds from Pistacia atlantica Desf. leaves are studied for their potential activity against the novel virus by inhibiting two key enzymes in its life cycle, and no further studies have been published in this context.
Keywords: RNA-dependent RNA polymerase